Implementation of Green Accounting and Material Flow Cost Accounting in Supporting Sustainable Development - Fani Artamevia Pamudya; Riz Yudha Tama; Anna Summaryati (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2025)
This study aims to examine the influence of green accounting and material flow cost accounting on sustainable development in palm oil companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2023. The sample consists of five companies observed over a nine-year period, resulting in a total of 45 data points. The analysis was conducted using WarpPLS version 7.0, including model fit testing, the calculation of the coefficient of determination, predictive relevance assessment, and hypothesis testing. The findings reveal that both green accounting and material flow cost accounting have a significant effect on sustainable development in the palm oil industry.